Dondy Tan’s Da‘wah Model on Christology: A Virtual Ethnography Study - Musadad, Ahmad; Mohammad Ali Hisyam; Baihaqi; Mochamad Syaifudin; Tri Pujiati; Fauzi, Alfa Zaidanil (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2025)
The digital da‘wah increasingly occupies an important place in contemporary Islamic studies, particularly amid growing interfaith interaction and media cultural transformation. This article examines an emerging da‘wah model of Christology developed by Dondy Tan, a Chinese Indonesian Muslim convert. His da‘wah has attracted significant attention among Indonesians, particularly among those seeking to deepen their interfaith theological awareness. This research employs a qualitative digital ethnography with a descriptive-analytical design. The data is mainly collected from Dondy Tan’s YouTube channel, podcasts, and related media sources from 2023 to 2025. In addition, the theoretical frameworks of media convergence, interreligious dialogue, and identity transformation are used to analyze and interpret the phenomenon of digital da‘wah. This study found that Dondy Tan’s da‘wah on Christology is a transformative convergent da‘wah: it converges digital technology and active virtual participation, creating an inclusive and moderate interreligious debate and dialogue, and it transforms individuals, as the da‘wah is institutionally providing religious counselling and social commitment for converts.